Pharmacogenetic studies of long-acting beta agonist and inhaled corticosteroid responsiveness in randomised controlled trials of individuals of African descent with asthma. (December 2021) - Ortega, Victor E; Daya, Michelle; Szefler, Stanley J; Bleecker, Eugene R; Chinchilli, Vernon M; Phipatanakul, Wanda; Mauger, Dave; Martinez, Fernando D; Herrera-Luis, Esther; Pino-Yanes, Maria; Hawkins, Gregory A; Ampleford, Elizabeth J; et al.
Summary: Background: Pharmacogenetic studies in asthma cohorts, primarily made up of White people of European descent, have identified loci associated with response to inhaled beta agonists and corticosteroids (ICSs). Differences exist in how individuals from different ancestral backgrounds respond to long-acting beta agonist (LABA) and ICSs. Therefore, we sought to understand the pharmacogenetic mechanisms regulating therapeutic responsiveness in individuals of African descent. Methods: We did ancestry-based pharmacogenetic studies of children (aged 5–11 years) and adolescents and adults (aged 12–69 years) from the Best African Response to Drug (BARD) trials, in which participants with asthma uncontrolled with low-dose ICS (fluticasone propionate 50 μg in children, 100 μg in adolescents and adults) received different step-up combination therapies. The hierarchal composite outcome of pairwise superior responsiveness in BARD was based on asthma exacerbations, a 31-day difference in annualised asthma-control days, or a 5% difference in percentage predicted FEV1 . We did whole-genome admixture mapping of 15 159 ancestral segments within 312 independent regions, stratified by the two age groups. The two co-primary outcome comparisons were the step up from low-dose ICS to the quintuple dose of ICS (5 × ICS: 250 μg twice daily in children and 500 μg twice daily in adolescents and adults) versus double dose (2–2·5 × ICS: 100 μg twice daily in children, 250 μg twice daily in adolescents and adults), and 5 × ICS versus 100 μg fluticasone plus a LABA (salmeterol 50 μg twice daily). We used a genome-wide significance threshold of p<1·6 × 10 −4, and tested for replication using independent cohorts of individuals of African descent with asthma. Findings: We included 249 unrelated children and 267 unrelated adolescents and adults in the BARD pharmacogenetic analysis. In children, we identified a significant admixture mapping peak for superior responsiveness to 5 × ICS versus 100 μg fluticasone plus salmeterol on chromosome 12 (odds ratio [ORlocal African ] 3·95, 95% CI 2·02–7·72, p=6·1 × 10 −5 ) fine mapped to a locus adjacent to RNFT2 and NOS1 (rs73399224, ORallele dose 0·17, 95% CI 0·07–0·42, p=8·4 × 10 −5 ). In adolescents and adults, we identified a peak for superior responsiveness to 5 × ICS versus 2·5 × ICS on chromosome 22 (ORlocal African 3·35, 1·98–5·67, p=6·8 × 10 −6 ) containing a locus adjacent to TPST2 (rs5752429, ORallele dose 0·21, 0·09–0·52, p=5·7 × 10 −4 ). We replicated rs5752429 and nominally replicated rs73399224 in independent African American cohorts. Interpretation: BARD is the first genome-wide pharmacogenetic study of LABA and ICS response in clinical trials of individuals of African descent to detect and replicate genome-wide significant loci. Admixture mapping of the composite BARD trial outcome enabled the identification of novel pharmacogenetic variation accounting for differential therapeutic responses in people of African descent with asthma. Funding: National Institutes of Health, National Heart, Lung, and Blood Institute.